Effect of dust storm intensity variations on total path attenuation prediction - Elsheikh, Elfatih A A; Islam, Md Rafiqul; Habaebi, Mohamed Hadi; Zyoud, Ahareth; Suliman, F M; Eltahir, E I; Nadir, W A (IEEE, 2022)
This paper proposes a novel dust-storm total path attenuation prediction model. This model is formulated as a function of specific attenuation (dB/km) and the effective distance, which considers the non-uniform dust storm intensity variations throughout the link. The effective distance is obtained as a combination of the total link distance and the reduction factor. The reduction factor is developed based on the modeled 2-D structure of the observed dust storm characteristics. A measurement campaign of atmospheric characteristics, their properties, and effects on several microwave links operated in Khartoum-Sudan was conducted. In an earlier report, an empirical dust storm attenuation prediction model was proposed based on short-distance links by assuming uniform dust storm intensity variations. However, it was observed that the dust intensity varies with the distance, which affects total attenuation, and this issue is not addressed yet. One year measurement on the 6.2 km and 7.6 km long microwave links operating at 21.2 GHz and 14.5 GHz are used to validate the proposed dust storm total path attenuation model.